2009
DOI: 10.1007/s10903-009-9274-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Barriers and Facilitators of Colorectal Cancer Screening Among Low Income Immigrant Hispanics

Abstract: Correspondence to: Lina Jandorf, lina.jandorf@mssm.edu. NIH Public Access

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
101
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(116 citation statements)
references
References 33 publications
11
101
4
Order By: Relevance
“…Differences in CRC screening between Hispanic and non-Hispanic Californian men have been well documented. [21][22][23][24] CRC screening rates among Mexican and South and Central American Hispanic males, the main Hispanic subgroups in California, are the lowest of any race/ethnic group in the country (39% and 35% respectively). 25 Cultural values and access to healthcare may explain lower rates of cancer screening among Hispanics in California.…”
Section: Rates Among Hispanics Did Not Decline Until 2008 (Table 2)mentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in CRC screening between Hispanic and non-Hispanic Californian men have been well documented. [21][22][23][24] CRC screening rates among Mexican and South and Central American Hispanic males, the main Hispanic subgroups in California, are the lowest of any race/ethnic group in the country (39% and 35% respectively). 25 Cultural values and access to healthcare may explain lower rates of cancer screening among Hispanics in California.…”
Section: Rates Among Hispanics Did Not Decline Until 2008 (Table 2)mentioning
confidence: 99%
“…Hispanic men are more likely to be uninsured or have Medicaid health insurance, and are less likely to have a primary care provider, all of which decrease the likelihood of CRC screening. 23,26 Limited language proficiency may be an additional barrier.…”
Section: Rates Among Hispanics Did Not Decline Until 2008 (Table 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] However, its effectiveness for reducing CRC mortality for vulnerable populations is unclear, given the barriers to colonoscopy, including cost, transportation problems, preparing for the procedure, and fear of invasive tests. [5][6][7][8][9][10][11][12] Expanded use of FOBT, a modality with fewer barriers, may be a viable approach to address CRC screening disparities, especially with single-sample fecal immunochemical tests (FIT), which do not require dietary restrictions. 13 Several randomized trials have reported that outreach with FOBT can improve CRC screening rates.…”
Section: Introductionmentioning
confidence: 99%
“…compared foreign-born Hispanic (Jandorf et al, 2010), Asian (Misra, Menon, Vadaparampil, & BeLue, 2011), and non-Hispanic Black (Odedina et al, 2011) men with their U.S.-born counterparts (Argeseanu Cunningham et al, 2008). However, the research is limited when comparing U.S.-and foreign-born non-Hispanic Whites.…”
mentioning
confidence: 99%